Alternative communication technologies for correcting speech impairment in children with autism spectrum disorders - S.N. Komarova; I.A. Nigmatullina (Ученые записки Казанского университета: Серия Гуманитарные науки)
In recent years, both in Russia and other countries, the number of children with autism spectrum disorders (ASD) has increased. The most relevant but still little-studied is the problem of finding and using alternative technologies that could be efficient in educating and raising such children, including their speech habilitation. This article reviews the advances made by Russian and foreign researchers in using alternative communication technologies, as well as provides numerous examples of various modern alternative communication methods and how their systematic dosed use through verbal and non-verbal communication helps to correct many speech and communication-related problems faced by children diagnosed with ASD. The correlation and development of verbal and non-verbal means of communication are considered with an account of the historical context of their interaction. The possibility and appropriateness of using non-verbal communication for educating children having ASD are discussed. A classification of methods and means of alternative communication is introduced. Three systems of alternative communication (gestural, graphic (symbolic), and assistive (hardware and/or software)) are qualitatively described. Their potential for developing speech and communication skills in children with ASD is analyzed. Recommendations for choosing an appropriate means of communication based on the children's initial fine motor skills, primary communication skills (if any), level of visual perception, motivational factors, and interests are presented.